1987
DOI: 10.1182/blood.v69.2.446.bloodjournal692446
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to discrete regions in alpha 2-plasmin inhibitor

Abstract: Three monoclonal antibodies to alpha 2-plasmin inhibitor (alpha 2PI) were characterized. The first, JTPI-1, was directed against the reative site of alpha 2PI and inhibited antiplasmin activity by interfering with the formation of alpha 2PI-plasmin complexes. The avidity of JTPI- 1 to the preformed alpha 2PI-plasmin complex was markedly lower than that to free alpha 2PI, which made this antibody useful for measuring the free alpha 2PI in plasma. The second, JTPI-2, recognized an epitope in the C-terminal fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Prothrombin fragment 1 +2 (F1+2) was measured by a sandwich ELISA (Enzygnost-F1+2, Behringwerke AG, Marburg, Germany) [20]. Plasmin-a,-plasmin inhibitor complex (PIC) was measured by a one-step sandwich ELISA (PIC test, Teijin Ltd., Tokyo, Japan) using polyclonal antiplasminogen antibody-coated polystyrene balls and peroxidase-conjugated monoclonal antibody against a,-plasmin inhibitor [21,22]. Activated partial thromboplastin time (APTT), prothrombin time, fibrinogen, and platelet count were measured by standard methods.…”
Section: Assay Methodsmentioning
confidence: 99%
“…Prothrombin fragment 1 +2 (F1+2) was measured by a sandwich ELISA (Enzygnost-F1+2, Behringwerke AG, Marburg, Germany) [20]. Plasmin-a,-plasmin inhibitor complex (PIC) was measured by a one-step sandwich ELISA (PIC test, Teijin Ltd., Tokyo, Japan) using polyclonal antiplasminogen antibody-coated polystyrene balls and peroxidase-conjugated monoclonal antibody against a,-plasmin inhibitor [21,22]. Activated partial thromboplastin time (APTT), prothrombin time, fibrinogen, and platelet count were measured by standard methods.…”
Section: Assay Methodsmentioning
confidence: 99%
“…Human t-PA, PAI-1, and vitronectin were purified as described previously. 11,12 Human u-PA was a gift from Mochida Pharmaceutical (Tokyo, Japan). Monospecific antisera against u-PA, t-PA, and PAI-1 were prepared in rabbits as previously described 11 and immunopurified with each antigen immobilized on Sepharose 4B.…”
Section: Preparation and Characterization Of The Monoclonalmentioning
confidence: 99%
“…11,12 Human u-PA was a gift from Mochida Pharmaceutical (Tokyo, Japan). Monospecific antisera against u-PA, t-PA, and PAI-1 were prepared in rabbits as previously described 11 and immunopurified with each antigen immobilized on Sepharose 4B. Monoclonal antibodies against t-PA (JTA-1), u-PA (JSUK-2 and JSUK-5), PAI-1 (JTAI-3 and JTAI-4), and vitronectin (JFV-1, JYV-1) were prepared by the conventional method with BALB/c mice as previously described 13 and immunopurified as described above.…”
Section: Preparation and Characterization Of The Monoclonalmentioning
confidence: 99%
“…A previous study [5] has shown that early diagnosis and treatment of DIC improve clinical outcome. Although the usefulness of hemostatic molecular markers such as thrombin-antithrombin complex (TAT) [6], plasmin plasmininhibitor complex (PPIC) [7], and soluble fibrin (SF) [8] for the early diagnosis of DIC has been reported, such measurements are expensive and time-consuming. In Japan, DIC patients are usually treated with heparin [9] or with gabexate mesilate (FOY), a synthetic protease inhibitor [10] that inhibits the activity of thrombin, Factor Xa, plasmin, and plasma kallikrein.…”
Section: Introductionmentioning
confidence: 99%